Influence of a Diester Glucocorticoid Spray on the Cortisol Level and the CCR4+ CD4+ Lymphocytes in Dogs with Atopic Dermatitis: Open Study. (21st September 2014) - Fujimura, Masato; Ishimaru, Hironobu
Abstract : This study investigated the influence of 0.00584% hydrocortisone aceponate spray (HCA; Cortavance Virbac SA, Carros, France) on blood serum cortisol levels and peripheral blood CCR4 + CD4 + T-lymphocyte levels in dogs with atopic dermatitis. Patients were randomly divided into group I (N = 8 ) and group II (N = 8 ). The dogs in group I were sprayed with HCA on the affected skin once a day for three weeks. The dogs in group II were treated once a day for 3 days followed by no treatment for 4 days for a total of three weeks. For the dogs in group I and group II the CADESI-03 scores before and after use of HCA showed significant reduction (P < 0.01 ). The postcortisol level after the use of HCA in group I showed 36.0% decrease and showed significant suppression (P < 0.01 ). By comparison, the use of HCA on group II did not show decrease in postcortisol levels. There was a tendency of suppression for hypothalamus—pituitary gland—adrenal gland system, but it was not serious influence. In addition, there was no influence on peripheral blood CCR4 + CD4 + lymphocytes percentage in dogs in group I after treatment with HCA.